Tree‐ring‐based precipitation reconstruction in the source region of Weihe River, northwest China since AD 1810 - Changfeng Sun; Yu Liu; Huiming Song; Ruochen Mei; Paramate Payomrat; Lu Wang; Ruoshi Liu (International Journal of Climatology, 2018)
A tree‐ring width chronology of Picea purpurea Mast from Mt. Shouyang in the source region of Weihe River (SWR), northwest China, was developed in this study. Correlation analysis showed that the precipitation from previous August to current July was the limiting climate factor of tree growth. Using a reliable and stable linear regression model, which explained 42.6% of the variance of the actual precipitation during the calibration period from 1958 to 2014, a 205‐year long precipitation series was reconstructed for the SWR. The dry years in the reconstruction were well supported by historical documents, and famous historical droughts were also recorded in the dry periods of a low‐frequency scale of the reconstructed precipitation. As demonstrated by the spatial correlation patterns, the reconstructed series compared well with other hydroclimate records for northwest China, indicating that it could represent large‐scale hydroclimate changes. The 2–8‐year interannual cycles and the interdecadal quasiperiods of 15.9 years and 18.6 years revealed that the precipitation in this region was probably affected by the El Niño‐Southern Oscillation and North Atlantic Oscillation. The dry/wet years corresponded well with the El Niño/La Niña events and the SWR commonly experienced droughts during the low periods of North Atlantic Oscillation.